The Relationship of the Strategies and Practices of the School Heads and Master Teachers and Teachers’ Competencies and Skills in the New Normal - Noruel M. Donato (International Journal of Theory and Application in Elementary and Secondary School Education, 2021)
Monitoring and supervision are essential practices of the school leaders to determine the various aspects of the school’s performance as well as teacher's competencies. This study aimed to determine the relationship between the monitoring and supervision strategies and practices of School heads and Master teachers and teachers’ competencies and skills in the new normal. The study employed a descriptive-correlational explanatory research design to determine the correlation between the variables. A stratified sampling method was utilized to select the respondents. A total of 385 teachers and 267 school heads and master teachers were the respondents of the study. A survey questionnaire was the primary data gathering instrument. Results of the study show that there is a relationship between the school heads and master teacher's practices and strategies. It also reveals that observance of school heads and master teacher's practices of monitoring and supervision of teachers has a relationship to teachers' competencies and skills. In addition, only staff development influences teachers' competencies and skills. The researcher recommended that the school heads and master teachers may continuously attend professional development activities to further improve some of their strategies and practices in monitoring and supervising teachers and to acquire strategies that are applicable and appropriate to the new normal; the school may offer and conduct activities that may improve and sustain the competencies and skills of teachers especially on the strategies and technology-aided materials and applications that can be used in teaching in distance learning.